Three Step Interview to Improve Studentsâ Speaking Ability in Islamic Higher Education of Bakti Negara Tegal - Kaptiningrum, Pindha (Proceeding of International Conference on Teacher Training and Education, 2016)
Students have been flooded with reading and grammar materials from many resources, especially from the module, the book, eBook and online resources. Not all English aspects have been taught at class. Theresearcher has tried to improve the studentsâ speaking ability by using three step interview. Three stepinterview was a cooperative learning that the students interview their partners by asking the given theme.Then, partners have switched the roles. For the final step, students have shared the result of interview withtheir partner. This research was an action research aiming at applying three step interview to improvestudentsâ English ability. Thus, the researcher has used test to measure the studentsâ speaking ability. Theresult of analyses has shown that in general studentsâ speaking ability in terms of the overall impression oftheir speaking, their fluency, their pronunciation, their grammar and vocabulary, and content/message in thetwo cycles have improved, particularly in cycles I and II.